Painting in XVIII century Venice - Levey, Michael (Phaidon Press, 1959)
Contents: First edition paperback (Phaidon Publishers, 1959). Minimal shelf wear; some foxing on flyleaf. Aside from slight age-related tanning, this book is in near-perfect condition with no marks, tears, stains, or highlighting; binding is tight and solid